Expression, Characterization, Fermentation, Immobilization, and Application of a Novel Esterase Est804 From Metagenomic Library in Pesticide Degradation - Chen, Cuihua; Yu, Gen; Guo, Zhenyu; Yang, Qihao; Su, Wenfeng; Xie, Qingfen; Yang, Guandong; Ren, Yifei; Li, He (Frontiers in Microbiology, 2022)
Esterase, as the type of powerful catabolic enzyme for pyrethroid pesticides (PYRs), appear promising in improving the quality of crops and environment contaminated by pesticides residues. The purpose of this research is giving a detail introduction on the enzymatic properties, optimal production and immobilization conditions and the degradation ability of Est804 for PYRs. The study on enzymatic properties indicated that Est804 was an alkaline esterase with an optimal pH of 8.0 and a broad optimal temperature in the range of 35-50℃. The optimal activity of free Est804 was calculated to be 112.812 U and the specific enzyme activity was 48.97 U/mg. The kinetic parameters of Est804 were Km=0.613 mM, kcat=12,371 s-1 and Vm=0.095 mM/min. The results of the fermentative optimization demonstrated that the optimal conditions was made up of 1.5% of inoculation amount, 30mL of liquid volume, 28℃ of the fermentation temperature and 18 h of the fermentation time. The optimal medium consists of 15.87 g of yeast powder, 8.00 g of glycerol, 9.57 g of tryptone in each liter liquid. The optimized enzyme activity was 1.68 folds higher than that before optimization. Immobilized Est804 exhibited the highest activity under the optimum preparation conditions including 0.35 g chitosan dosage, 0.4 mL enzyme amount, 4 h at 40℃ for adsorption. The degradation rates of CYP, FE and LCT by Est804 within 30 min were 77.35%, 84.73% and 74.16%, respectively. The present work of our research indicated that Est804 possesses a great potential for the treatment of pesticide residues on crops and environmental remediation, conducing to the development of SGNH family esterase against pyrethroid accumulation.